Copper Nitride Nanowires Printed Li with Stable Cycling for Li Metal Batteries in Carbonate Electrolytes. Issue 7 (12th January 2020) - Lee, Dongsoo; Sun, Seho; Kwon, Jiseok; Park, Hyunjung; Jang, Minchul; Park, Eunkyung; Son, Byoungkuk; Jung, Yeongil; Song, Taeseup; Paik, Ungyu
Abstract: The practical implementation of the lithium metal anode is hindered by obstacles such as Li dendrite growth, large volume changes, and poor lifespan. Here, copper nitride nanowires (Cu3 N NWs) printed Li by a facile and low‐cost roll‐press method is reported, to operate in carbonate electrolytes for high‐voltage cathode materials. Through one‐step roll pressing, Cu3 N NWs can be conformally printed onto the Li metal surface, and form a Li3 N@Cu NWs layer on the Li metal. The Li3 N@Cu NWs layer can assist homogeneous Li‐ion flux with the 3D channel structure, as well as the high Li‐ion conductivity of the Li3 N. With those beneficial effects, the Li3 N@Cu NWs layer can guide Li to deposit into a dense and planar structure without Li‐dendrite growth. Li metal with Li3 N@Cu NWs protection layer exhibits outstanding cycling performances even at a high current density of 5.0 mA cm −2 with low overpotentials in Li symmetric cells. Furthermore, the stable cyclability and improved rate capability can be realized in a full cell using LiCoO2 over 300 cycles. When decoupling the irreversible reactions of the cathode using Li4 Ti5 O12, stable cycling performance over 1000 cycles can be achieved at a practical current density of ≈2 mA cm −2 . Abstract : A Li3 N@Cu nanowires (NWs) protection layer is formed by roll‐pressing the sandwiched Li/Cu3 N NWs foil together. Li3 N@Cu NWs–Li is proposed as a modified Li‐metal anode to regulate uniform Li‐ion flux on the interface between a Li‐metal anode and a liquid electrolyte for stable Li‐metal batteries.